Online Learning Objects in higher education, an alternative in times of pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research was to describe the benefits of Online Learning Objects asdidactic strategies for teaching and learning in higher education in times of pandemic. Themethodology used was based on the qualitative paradigm, applying the deductive method; thetype of research was descriptive bibliographic documentary, through content analysis ofscientific articles and research papers as the basis of the study. The analysis of the results wascarried out through content analysis according to categories of research interest. It waspossible to establish several advantages and benefits associated with the use of OnlineLearning Objects to improve the teaching-learning process in different areas of highereducation, especially in times of pandemic.